Foreign language anxiety among pre-service teachers of french language In selected tertiary institutions in South Western Nigeria (2017)
The study examined the influence of anxiety on the success of some pre-service teachers of French Language in selected tertiary institutions in southwestern Nigeria. Descriptive research design was adopted. A total of 130 preservice teachers (male — 40 and female — 90) participated in the study. The results showed that the test anxiety level of pre-service teachers' foreign language anxiety is slightly low (X = 2.32, Std. Dev = 1.162). The findings further showed that the fear of negative evaluation level of pre-service teachers' foreign language anxiety is a bit high (X = 2.65, Std. Dev = 1.227). Data collected were analysed using PPMC and Regression Analysis. The results showed that the communication apprehension level of pre-service teachers' foreign language anxiety was slightly low (X = 2.29, Std. Dev — 1.188). There was no influence of age on pre-service teachers’ foreign language anxiety in classroom (F value —1.349, P>0.05). There was no gender difference in the pre-service teachers’ foreign language anxiety in classroom (t-Critical value (t-Crit—1.99, P>0.05). Length of years of French study had no influence on the pre-service teachers’ foreign language anxiety in classroom (F value — 1.349, Pro— 0.262>0.05). It was however recommended that pre-service teachers of French language in tertiary institutions should pay maximum attention to the variants of foreign language anxiety of fear of negative evaluation, communication apprehension and test anxiety in the process of learning French language as a foreign language.